Appropriateness, Acceptability, and Feasibility of a Neurodiversity-Based Self-determination Program for Autistic Adults. - McDonald, T. A. Meridian; Lalani, Salima; Chen, Ivy; Cotton, Claire M.; MacDonald, Lydia; Boursoulian, Lana J.; Wang, Jiahao; Malow, Beth A. (Journal of Autism & Developmental Disorders, 2023)
Published self-determination programs do not adequately address the needs of autistic adults. We designed a multi-component self-determination program, grounded in the neurodiversity paradigm, to help autistic adults achieve goals to improve their quality of life. The first phase involved 5 days of psychoeducation, practice, and social events; the second phase included 3 months of telecoaching; and the third phase included follow-up. Thirty-four university students coached 31 autistic adults on three evolving goals. On average, participants completed one goal per week. Most participants were satisfied with the program. We found that the program was appropriate, acceptable, and feasible. This program is a promising approach to helping autistic adults gain self-determination skills and improve their quality of life.